Enhanced hybrid hydrogel based on wheat husk lignin-rich nanocellulose for effective dye removal - Huang, Rong; Xu, Yong; Kuznetsov, Boris N.; Sun, Meitao; Zhou, Xin; Luo, Jing; Jiang, Kankan (Frontiers in Bioengineering and Biotechnology, 2023)
Polyvinyl alcohol (PVA) hydrogels were enhanced mechanically through the addition of lignin-rich nanocellulose (LCN), soluble ash (SA) and montmorillonite (MMT) for dye removal. The hybrid hydrogels reinforced with 33.3 wt% of LCN had a 163.0% increase in storage modulus as compared to the PVA/0LCN-33.3SM hydrogel. LCN can be added to the PVA hydrogel to alter its rheological properties. Additionally, hybrid hydrogels were highly efficient in removing methylene blue from wastewater, which was attributed to the synergistic effects of the PVA matrix supporting embedded LCN, MMT, and SA. The adsorption time (0~90 min) showed that the hydrogels containing MMT and SA had high removal efficiency, and the adsorption of MB by PVA/20LCN-13.3SM was greater than 95.7% at 30 ℃. It was found that MB efficiency decreased with a high MMT and SA content.